2009
DOI: 10.1073/pnas.0900328106
|View full text |Cite
|
Sign up to set email alerts
|

A unique basaltic micrometeorite expands the inventory of solar system planetary crusts

Abstract: Micrometeorites with diameter Ϸ100 -200 m dominate the flux of extraterrestrial matter on Earth. The vast majority of micrometeorites are chemically, mineralogically, and isotopically related to carbonaceous chondrites, which amount to only 2.5% of meteorite falls. Here, we report the discovery of the first basaltic micrometeorite (MM40). This micrometeorite is unlike any other basalt known in the solar system as revealed by isotopic data, mineral chemistry, and trace element abundances. The discovery of a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 41 publications
2
50
0
Order By: Relevance
“…-it is now well established that basaltic achondrites derived from a number of parent bodies (Yamaguchi et al, 2001;Scott et al, 2008;Gounelle et al, 2009) -the Fe/Mn ratios of the spherules are consistent with a link to the HEDs; moreover, the occurrence of an unmelted diogenitic remnant in a high K-spherule strongly strengthens this conclusion (Barrat et al, 2009a).…”
Section: Origin Of the Unusual Trace Element Patterns Of The High-k Smentioning
confidence: 90%
“…-it is now well established that basaltic achondrites derived from a number of parent bodies (Yamaguchi et al, 2001;Scott et al, 2008;Gounelle et al, 2009) -the Fe/Mn ratios of the spherules are consistent with a link to the HEDs; moreover, the occurrence of an unmelted diogenitic remnant in a high K-spherule strongly strengthens this conclusion (Barrat et al, 2009a).…”
Section: Origin Of the Unusual Trace Element Patterns Of The High-k Smentioning
confidence: 90%
“…The latter age is earlier than the differentiation age inferred by Goodrich et al (2010) for ureilites and may imply that feldspathic clasts date later crustal processing rather than parent-body differentiation. Gounelle et al (2009) reported that a basaltic micrometeorite has no excess 26 Mg in plagioclase with high Al/Mg ratios, giving an upper limit for the 26 Al/ 27 Al at the time of formation of <2.8 Â 10 À7 , implying formation more that 7.9 Ma after CAI formation.…”
Section: Al-26 Mg Systematics In Achondritesmentioning
confidence: 99%
“…The size of most of the dust ranges from a few μm to a few mm. A significant aspect of micrometeorite studies is that some of these particles may have sampled unfamiliar asteroids that are not represented in our meteorite collection (Yada et al 2005;Gounelle et al 2009). The dust particles are anticipated to originate predominantly in the asteroid belt anddrift further-into the inner solar system with a large probability of getting trapped in orbital resonance with Earth due to their smaller orbital eccentricities compared to cometary particles (Dermott et al 1994;Reach et al 1997;Brownlee 2001, pp.…”
Section: Introductionmentioning
confidence: 99%